Pelatihan Penyuntingan Karya Tulis Ilmiah Populer Untuk Siswa Kelas XII SMA Negeri 1 Kedamean - Pana Pramulia; Mimas Ardhianti; Sri Budi Astuti (Universitas Maritim AMNI Semarang, 2024)
One form of writing, namely popular scientific works. In writing popular scientific works, writers must follow predetermined guidelines, for example templates, word choice (diction), and suitability of themes. Popular scientific works have word choices that are easy to read and easy for various groups to understand. Therefore, an editing process is needed so that popular scientific works become good. The aim of editing is to avoid too many errors and add references if necessary. Editing is the author's final step before his writing is published. Editing is not an easy job. This was experienced by the students of SMA Negeri 1 Kedamean. For this reason, lecturers in the Indonesian Language Education Study Program at PGRI Adi Buana University Surabaya need to provide community service through training. Training implementation method with face-to-face presentations, modeling and simulation accompanied by assignments. The community service carried out can provide students with insight and skills in editing popular scientific papers.